The Role of Online Marketing Media on Airline Ticket Purchasing Decisions - Sari, Mustika; Abdurrahman, Edi; Mafrudoh, Lut; Basuki, Friska Balqist (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aimed to determine the effect of social media, influences, and brand image on purchasing decisions. The method used in this research is quantitative-descriptive. The population in this study were consumers who had purchased Jetstar Asia airline tickets in 2022. In this study, we used the probability sampling technique with the simple random sampling method, namely with a sample size of 160 respondents. The analysis method in this study uses SEM-PLS with the SmartPLS 3.0 application. The results of this study state that social media has a positive and significant effect on purchasing decisions, influences have a positive and significant impact on buying decisions, and brand image has a positive and significant effect on buying decisions.